Exploring the Use of Artificial Intelligence-based Technology to Enhance Creativity in ESL Speaking Classroom - Hazwani, Hassim; Hafizoah, Kassim; Asiah, Kassim; Murizah, Kassim (IEEE Xplore, 2023)
This paper reports a quantitative study, which investigated the application of SpeechAce, an artificial intelligence-based platform, in English as a Second Language classrooms at a secondary school in Johor, Malaysia. The research aims to address the current challenges in enhancing speaking English proficiency and promoting creativity among 30 ESL learners. Data were collected using a pre-post-intervention assessment, student questionnaires, and classroom observations. Standardized tests, such as the Torrance Tests of Creative Thinking and the TOEFL iBT, were used to assess students’ speaking skills and creativity, respectively, with the Foreign Language Classroom Anxiety Scale (FLCAS) employed to assess students' anxiety levels. The collected data were subjected to rigorous statistical and thematic analysis. The study's findings aim to contribute to the existing literature on AI in language learning and provide actionable insights for the integration of AI technology into ESL classrooms to enhance creativity and fluency.